Kajian Pengaruh Pelebaran Sungai terhadap Debit Aliran - Ryan Prayogi; Azwarman Azwarman; Susiana Susiana (Universitas Batanghari, 2023)
Flood is one of the problems that often occurs in Indonesia. In Jambi City, every rainy season often experiences flooding, especially in Jambi City or the Garuda III Jaya Complex area, Bagan Pete Village, Jambi City. Thus, this study aims to determine how much rainfall intensity is on the Kenali Besar River and how much river flood discharge has been carried out at Komplek.Perum Garuda III Jaya, Bagan Bete Village, Jambi City with a time of 10 years and so that later the Kenali Besar River channel can be channeled. can function optimally to reduce flooding that occurs in the Garuda III Jaya Complex area, Bagan Pete Village, Jambi City, so that a good and quality river is created while taking into account the safety and comfort factors for the surrounding community. In this study, the data used were secondary data in the form of daily rainfall for 10 years and cross-sectional dimension data of the Kenali Besar River Komplek.Perum Garuda III Jaya, Bagan Pete Village. The results of the calculation of the planned rain with a return period of 10 years is 246.469 mm⁄hour, while the planned discharge using the Rational method obtained a peak discharge value of 30.833 m3⁄seconds the step is continued using HEC-RAS 5.0.7 software to determine the capacity of the drainage channel by using plan debit. After being analyzed using software.